Effects of Redundancy and Modality Principle in Multimedia Learning: Concentration on Motivation and Gender DIfferences among Primary School Students - Perng Jeu Ng; Mariam Mohamad (Pejabat Karang Mengarang UPSI, 2019)
This aim of this study is to examine the impact of on-screen text on the learning performance of grammar learning of Bahasa Malaysia involving a group of primary schoolers. In addition, learners' characteristics such as motivation and gender were also examined in this study. It was hypothesized that learners who had received redundant text explanation and animation would perform worse on memory and problem solving test. Results showed that the redundancy learning mode that integrates animation, sound narration and on-screen text in a computer-based environment helped improve students' performance. This finding suggests that on-screen text could reduce cognitive load and enhance learning process, which leads to better performance.